Principal’s Strategy in Improving Educational Quality - J, Fitria; Arafat, Yasir; Furqan, Nuril (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
The purpose of this research is to discover (1) the principal’s plan for improving educational quality; and (2) the challenges and solutions for executing the principal’s strategy at Bukit Asam Tanjung Enim Muara Enim High School in South Sumatra. A descriptive qualitative technique was used in this investigation. The school principal is the focus of this study. Data were gathered through interviews, observation, and documentation. Data triangulation is used to determine the validity of the data. Milles and Huberman’s interactive analysis was employed as the analytical model. According to the research, the principal’s plan at SMA Bukit Asam Tanjung Enim Muara Enim South Sumatra has a reference, especially by looking at the 8 National Education standards. Attempts to increase the quality of education for school principals via collaboration in the health sector (PMI and local public health center); public universities; tutoring; state apparatus (civil and military resort command); and the surrounding community. Teachers who did not support and limited communication were hurdles. Teacher training and online communication are the necessary solutions.